Korelasi antara Belajar Mandiri dengan Prestasi Belajar Bahasa Jerman pada Kemampuan Membaca - Nurvaeni Kamal; Mantasiah R; Hasmawati Hasmawati (Academic : Journal of Social and Educational Studies, 2022)
Abstract. This study aims to obtain data and information about the correlation between independent learning and German language learning achievement on the reading ability for class XI students of SMA Negeri 1 Bone. The population in this study was the entire class XI IBB SMA Negeri 1 Bone, amounting to 26 people an at the sam time as the research sample. The data from this study were obtained from the Likert Skala and reading ability tests. Basend on the result of the Product moment correlation data analysis, it shows that the R counts is smaller than the R table. The result of data analysis showed that there was a significant relationship between independent learning and learning achievement in German on the reading ability of XI grade students of SMA Negeri 1 Bone, but it was weak.Keywords: Learn to Be Independent, Learning Achievement, German Language